2019
DOI: 10.1071/fp18278
|View full text |Cite
|
Sign up to set email alerts
|

The role of jasmonate signalling in quinolizidine alkaloid biosynthesis, wounding and aphid predation response in narrow-leafed lupin

Abstract: Quinolizidine alkaloids (QAs) are toxic secondary metabolites produced in lupin species that protect the plant against insects. They form in vegetative tissues and accumulate to a different extent in the grains: high levels in ‘bitter’ narrow-leafed lupin (NLL) and low levels in ‘sweet’ NLL. Grain QA levels vary considerably, and sometimes exceed the industry limit for food and feed purposes. We hypothesised that jasmonates regulate QA biosynthesis in response to environmental stresses such as wounding and aph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…While NLL is emerging as a human health food, toxic specialised metabolites of the quinolizidine alkaloids class are required to remain below a 0.02% threshold in the grain for it to be used for food or feed purposes (Frick et al., 2017). A picture is emerging in which environmental stresses cause an increase in alkaloids in the NLL leaves and grain (Frick et al., 2018; Frick et al., 2019), but independent studies have identified different candidate genes for the key alkaloid regulatory locus iucundus (Kroc et al., 2019b; Wang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…While NLL is emerging as a human health food, toxic specialised metabolites of the quinolizidine alkaloids class are required to remain below a 0.02% threshold in the grain for it to be used for food or feed purposes (Frick et al., 2017). A picture is emerging in which environmental stresses cause an increase in alkaloids in the NLL leaves and grain (Frick et al., 2018; Frick et al., 2019), but independent studies have identified different candidate genes for the key alkaloid regulatory locus iucundus (Kroc et al., 2019b; Wang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Ca 2+ can activate enzyme LOX6, which participates in the JA synthesis [ 41 ]. Additionally, stimulation of the JA production after mechanical damage [ 42 ] can be caused changes in activity of the phospholipase D [ 43 ]; it is known that this enzyme is activated by Ca 2+ influx [ 44 ]. Ways of influence of other signal molecules (ROS, H + ) on the phytohormones production are not clear; however, their effects can be potentially related to interactions between Ca 2+ , ROS and pH signal ways [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both drought and high temperature stress as well as their interaction could affect alkaloid content in the NLL grain, albeit in a genotype specific matter (Frick et al, 2018). In contrast aphid predation using the green peach aphid ( Myzus persicae ) did not exhibit changes in QA biosynthetic gene expression or grain QA content (Frick et al, 2019). In conclusion, a number of genes that contribute to QA biosynthesis and regulation have been identified (Frick et al, 2018, 2019; Kroc et al, 2019; Yang et al, 2017).…”
Section: Specific L Angustifolius Transcriptome Studies With a Focus On Seed Biology And Alkaloidsmentioning
confidence: 99%
“…In contrast aphid predation using the green peach aphid ( Myzus persicae ) did not exhibit changes in QA biosynthetic gene expression or grain QA content (Frick et al, 2019). In conclusion, a number of genes that contribute to QA biosynthesis and regulation have been identified (Frick et al, 2018, 2019; Kroc et al, 2019; Yang et al, 2017).…”
Section: Specific L Angustifolius Transcriptome Studies With a Focus On Seed Biology And Alkaloidsmentioning
confidence: 99%